Modelagem na Educação Matemática: implicações na formação do ser e do saber - Mazur, Maria (2021)
The present study had as an overall goal to investigate and analyze which contributions are shown, in relation to the individual and the knowledge of high school students, from the practices with Modeling in Mathematical Education. Starting from the general goal, the following specific objectives unfolded: to identify and analyze the actions and interactions of student participants through the practices with modeling; identify and analyze aspects of the daily lives of students participating in the research when proposing topics of their interests; to develop teaching material containing activities which involve practices with Modeling from the perspective of Mathematical Education. In order to meet the goals of this work, the research was conceived in a qualitative/interpretative perspective, as it presents the characteristics contributed by Bogdan and Biklen (1994). The data treatment of this research followed the assumptions of Bogdan and Biklen (1994), with the observation and understanding of the study phenomenon in the environment where it occurs, description of activities through observations and records in the field diary, photographs, audio recordings, spontaneous testimonies, interviews. There was a concern in conducting the teaching and learning process in an interactive way, in which, the researched data demonstrated the perspectives of work in a collaborative environment and the data analysis followed an inductive process through the inter-relationship between teacher and students. The results of this research demonstrate that the practices with Mathematical Modeling, from the perspective of Mathematical Education, contributed to the learning of mathematical content in an interdisciplinary way which also included some knowledge of Chemistry, Biology, pharmaceuticals and medicine. The contributions were also made in the scope of the formation of the individual as a critical researcher who is also autonomous, collaborative, persevering, enthusiastic, supportive, empathetic, interested in learning, capable of searching for knowledge and making decisions as well as capable of attributing sense and meaning to mathematical content.